“A chiare lettere - Confronti” • Ammissibile? Alcuni dubbi sul referendum fine vita (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Sulla chiarezza del quesito - 2. sul valore costituzionalmente necessario del suo oggetto - 3. sulla complessità dei suoi effetti di sistema.Admissible? A few doubts about the referendum end-of- lifeABSTRACT: Does the proposal of the referendum end-of-life in Italy infringe on the constitutionally protected right to the life? In the affirmative case the referendum would be inadmissible according to the constitutional jurisprudence. In this paper there are exposed a few doubts in this regard and also about the clarity of the question and the indirect effects on other rules, that reveal the complexities of the matter.